Effect of charted mental illness on reperfusion therapy in hospitalized patients with an acute myocardial infarction in Florida. Issue 34 (August 2017) - Campi, Thomas R.; George, Sharon; Villacís, Diego; Ward-Peterson, Melissa; Barengo, Noël C.; Zevallos, Juan C.
Abstract : Abstract: Patients with mental illness carry risk factors that predispose them to excess cardiovascular mortality from an acute myocardial infarction (AMI) compared to the general population. The aim of this study was to determine if patients with AMI and charted mental illness (CMI) received less reperfusion therapy following an AMI, compared to AMI patients without CMI in a recent sample population from Florida. A secondary analysis of data was conducted using the Florida Agency for Health Care Administration (FL-AHCA) hospital discharge registry. Adults hospitalized with an AMI from 01/01/2010 to 12/31/2015 were included for the analysis. The dependent variable was administration of reperfusion therapy (thrombolytic, percutaneous coronary intervention [PCI], and coronary artery bypass graft [CABG]), and the independent variable was the presence of CMI (depression, schizophrenia, and bipolar disorder). Multivariate logistic regression models were used to test the association controlling for age, gender, ethnicity, race, health insurance, and comorbidities. The database included 61, 614 adults (31.3% women) hospitalized with AMI in Florida. The CMI population comprised of 1036 patients (1.7%) who were on average 5 years younger than non-CMI (60.2 ±12.8 versus 65.2 ±14.1; P  < .001). Compared with patients without CMI, patients with CMI had higher proportions of women, governmental health insurance holders, and those with more comorbidities. The adjusted odds ratio indicated that patients with CMI were 30% less likely to receive reperfusion therapy compared with those without CMI (OR = 0.7; 95% CI = 0.6–0.8). Within the AMI population including those with and without CMI, women were 23% less likely to receive therapy than men; blacks were 26% less likely to receive reperfusion therapy than whites; and those holding government health insurances were between 20% and 40% less likely to receive reperfusion therapy than those with private health insurance. Patients with AMI and CMI were statistically significantly less likely to receive reperfusion therapy compared with patients without CMI. These findings highlight the need to implement AMI management care aimed to reduce disparities among medically vulnerable patients (those with CMI, women, blacks, and those with governmental health insurance).